2019
DOI: 10.21873/invivo.11629
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced NLRP3 and DEFA1B Expression During the Active Stage of Parenchymal Neuro-Behçet's Disease

Abstract: Background/Aim: Neurological symptoms (neuro-Behçet's disease; NBD) occur in a fraction of Behçet's disease (BD) patients and often present with parenchymal brain lesions and clinical exacerbations. Our aim was to identify genes associated with attack and remission periods of NBD. Materials and Methods: Microarray analysis was performed using peripheral blood mononuclear cell (PBMC) samples obtained during attack and remission periods of five NBD patients. Expression levels of the most significantly upregulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…It seems that an increased serum level of α-defensins 1-3 is due to increased α-defensins 1-3 load in primary granules of neutrophils and increased neutrophil degranulation not due to increased number of neutrophils [26]. Elif Ugurel et al [27] revealed that innate immunity is primarily involved in acute attacks of neuro-Behcet's disease (NBD) and treatment regimens attacking neutrophils might prove efficacy in the treatment of NBD and perhaps replace steroids that are already used for this disease.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that an increased serum level of α-defensins 1-3 is due to increased α-defensins 1-3 load in primary granules of neutrophils and increased neutrophil degranulation not due to increased number of neutrophils [26]. Elif Ugurel et al [27] revealed that innate immunity is primarily involved in acute attacks of neuro-Behcet's disease (NBD) and treatment regimens attacking neutrophils might prove efficacy in the treatment of NBD and perhaps replace steroids that are already used for this disease.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that IL-32 and NLRP3 inflammasome could be considered as potential biomarkers of vessel inflammation in NBD. Ugurel et al reported that during NBD attacks, the most remarkably up-regulated genes were defensin alpha 1B and NLRP3 [52]. Thus, NLRP3 can be used as a biomarker for estimation of disease activity in NBD.…”
Section: Key Pointsmentioning
confidence: 99%
“…NLRP12−/− mice developed exacerbated uveitis, which was not attributed to inherent T cell dysfunction but depended on enhanced neutrophil and macrophage accumulation, indicating that NLRP12 exerts an anti-inflammatory role to suppress uveitis [ 202 ]. In peripheral blood mononuclear cell samples of patients with Behçet’s disease, which is one of the uveitis-related chronic inflammatory diseases, NLRP3 expression level is upregulated during the onset of disease [ 203 ]. Genetic variants of NLRP3 and NLRP1 gene were found in patients suffering Behçet’s disease.…”
Section: Pyroptosis In Ocular Diseasesmentioning
confidence: 99%